Mixed Cu(i)/Au(i) coordination polymers as reversible turn-on vapoluminescent sensors for volatile thioethers. Issue 48 (1st June 2017) - Varju, Bryton R.; Ovens, Jeffrey S.; Leznoff, Daniel B.
Abstract : Cu(i )-doping transforms an inactive Cu(i )/Au(i ) coordination polymer into an emissive, reversible solid state sensor for dimethyl- and diethyl sulphide. Abstract : Vapour-phase thioethers play an important role in a wide number of fields, including plant biology, chemical weapon disposal, and brewing but few sensor materials are known. The emissive coordination polymer Cu1/2 Au1/2 CN does not react with vapour phase dimethyl sulphide (DMS) or diethyl sulphide (DES) despite the independent synthesis of emissive [Cu1/2 Au1/2 CN]2 (DMS) and [Cu1/2 Au1/2 CN]2 (DES) from their constituent components in solution. However, the doped Cu2/3 Au1/3 CN rapidly reacts in the solid state with both of these vapour phase thioethers reversibly, with a change in emission from 380/560 nm to 460 nm (DMS) or 420 nm (DES), illustrating that doping the inactive parent Cu1/2 Au1/2 CN with Cu(i ) generates an active sensor material. This response can be thermally cycled with little to no loss in functionality. [Cu1/2 Au1/2 CN]2 (DMS), [Cu2/3 Au1/3 CN]2 (DMS), and [Cu2/3 Au1/3 CN]2 (DES) were structurally characterized as 3-D network structures supported by aurophilic interactions.